Sosial Graph Isu Tolak Darurat Sipil di Media Sosial Twitter - Utama, Putu Kussa Laksana (Institut Hindu Dharma Denpasar, 2020)
The issue of rejecting civil emergency was widely discussed by Indonesian in late March to early April 2020. This was a response to the discourse on the implementation of civil emergency in the COVID-19 case presented by Indonesian president Mr. Joko Widodo. Although the execution was far from realization and was agreed to be picked up as a last resort choice in the context of COVID-19 countermeasures, this issue has caused a negative response sparked on sosial media shown by the emergence of hashtag #TolakDaruratSipil.This article aims to find out how the hashtag has developed on Twitter sosial media. By using the Sosial Network Analysis (SAN) approach, it will be known the pattern of the hashtag spreading on sosial media Twitter, how it is propagated on sosial media, and the users involved in spreading the hashtag. The results obtained in this study will be visualized in the form of Sosial Graph so that understanding of this issue can be more easily understood.